Analysis of President Prabowo's Foreign Policy : Indonesia's Existential Diplomacy in Joining of BRICS and OECD - Muhammad Ridha Iswardhana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Indonesia's decision to join BRICS as a full member on January 6, 2025, marks a significant shift in the direction of national foreign policy. Under the leadership of President Prabowo Subianto, this move is seen as a form of existential diplomacy aimed at asserting Indonesia's position in an increasingly multipolar global order. This study employs a descriptive qualitative approach with a case study method to examine the motives, processes, and impacts of this policy. It utilizes psychological theories of foreign policy and institutional liberalism to explain the case study. The analysis reveals that while BRICS membership opens strategic opportunities, the decision was not entirely based on domestic needs and leaves questions regarding the consistency of Indonesia's foreign policy direction. This study recommends further evaluation of symbolic foreign policies to ensure they align with long-term national interests.